If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2.2x-5.9+9x=9.2x-10.7
We move all terms to the left:
2.2x-5.9+9x-(9.2x-10.7)=0
We add all the numbers together, and all the variables
11.2x-(9.2x-10.7)-5.9=0
We get rid of parentheses
11.2x-9.2x+10.7-5.9=0
We add all the numbers together, and all the variables
2x+4.8=0
We move all terms containing x to the left, all other terms to the right
2x=-4.8
x=-4.8/2
x=-2+0.8/2
| -66=2(d-36) | | 3=7-c | | 11x+32-6x=-16-3x | | 1/1+x^2=0 | | 2x+2/3=8 | | 40=g/2+32 | | 15+3z=93 | | 4.1(x-2.7)=15.17 | | 75=95–z | | 96=2s+46 | | -21x+12x=3(-9-4x) | | 8k−5(−5k+3)=8k−5(−5k+3) | | 60–t=7 | | x2–x–3=0 | | -31-3x=212 | | 11x+28-6x=-21-2x | | 2x+-2x^-3=0 | | 3x+4-5=37 | | q=26+34 | | 65=3x-10 | | 25–3f=19 | | c9= 8 | | 4(2x+2)=40 | | 23+7p=72 | | 1a+6a=49 | | 15/28=45/x | | x^2+x^-2=0 | | b–23=24 | | -31-3x=12 | | 8j+13=29 | | x2=–7x–8 | | h+11=52 |